CRYPTO AS AN OBJECT OF CONTRACTUAL OBLIGATION UNDER THE REGULATION ON MARKETS IN CRYPTO ASSET (MICA) AND THE DIGITAL ASSETS ACT (DAA) - Cvetkovic, Mihajlo (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
The paper examines the legal status and treatment of crypto assets in the context of contractual obligations. The analysis begins by considering the evolution from cryptocurrencies to crypto-goods, with special reference to definitions and terms used in the context of private law transactions. Then, the author focuses on the contractual parties under the EU Regulation on Markets in Crypto Asset (MiCa, 2023) and the Serbian Digital Assets Act (DA Act, 2020), where crypto-assets are predominantly treated as investment assets. Special attention is given to e-money tokens in the context of monetary obligations, as well as to Non-fungible tokens (NFTs) that have not yet been covered by regulations. The paper also refers to the contracting of crypto services, exploring how contractual relationships are formed and regulated, and elaborating on legal transactions based on contracts within the blockchain environment and tokenization. In conclusion, the paper draws attention to the problematic terminology used in the Serbian Digital Assets Act (2020), stating that the term “digital asset” (srb. “digitalna imovina”) is too broad and inadequate, and proposes the term “crypto asset” (srb. “kripto dobro”) which is defined through two key elements: the private nature of the good and the use of cryptography within the Digital Ledger Technology (DLT). This paper correlates the general theory of contract law and nominate contracts when the contractor’s performance is in crypto.
Keywords: crypto; sale; NFT; token; contractual legal transaction; obligation